2011
DOI: 10.3892/ijo.2011.1304
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin induces apoptosis in vitro and inhibits tumor growth of human hepatocellular carcinoma cells in a nude mouse xenograft model

Abstract: Nonsteroidal anti-inflammatory drugs (NSAIDs) are known to induce apoptosis in a variety of cancer cells, including colon, prostate, breast and leukemia. Among them, aspirin, a classical NSAID, shows promise in cancer therapy in certain types of cancers. We hypothesized that aspirin might affect the growth of liver cancer cells since liver is the principal site for aspirin metabolism. Therefore, we investigated the effects of aspirin on the HepG2 human hepatocellular carcinoma cell line in vitro and the HepG2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
56
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 33 publications
7
56
0
Order By: Relevance
“…Interestingly, the size distribution of metastasis foci formed in WT mice treated with or without anti-platelet agents was of no significant difference, indicating that anti-platelet treatment had little direct effects on tumour cell growth and/or apoptosis. Although it is reported that high dose of aspirin 48 (100 mg kg À 1 per day) can reduce tumour burden and metastasis by direct tumour cell apoptosis and inhibition of angiogenesis, the low dose of aspirin used in our system (10 mg kg À 1 per day) is unlikely to cause such effects 43 . These data suggest that TLR4 deficiency may impair platelet activation during tumour metastasis.…”
Section: Discussionmentioning
confidence: 77%
“…Interestingly, the size distribution of metastasis foci formed in WT mice treated with or without anti-platelet agents was of no significant difference, indicating that anti-platelet treatment had little direct effects on tumour cell growth and/or apoptosis. Although it is reported that high dose of aspirin 48 (100 mg kg À 1 per day) can reduce tumour burden and metastasis by direct tumour cell apoptosis and inhibition of angiogenesis, the low dose of aspirin used in our system (10 mg kg À 1 per day) is unlikely to cause such effects 43 . These data suggest that TLR4 deficiency may impair platelet activation during tumour metastasis.…”
Section: Discussionmentioning
confidence: 77%
“…The spectrum of feasible therapies include cyclooxygenase inhibitors, proteaseactivated receptor inhibitors, and glycoprotein IIb/IIIa (GPIIb/IIIa) inhibitors. (6,12,(34)(35)(36) HCC patients with mild thrombocytopenia are likely better candidates until more scientific data on the safety of those therapies accumulate because such patients can have less bleeding diathesis and greater metastasis risk. In addition, the stable late posttransplant phase might provide another time window for targeting the latent metastasis with less concern about bleeding complications or graft regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…The anticancer activity of ASA is thought to be linked to their ability to inhibit cell proliferation and to induce apoptosis (7). We hypothesized that combination of ASA and DOX might be effective in the treatment of HCC since ASA has been reported to show anticancer effect on HCC (8,9). Therefore, the present study was designed to investigate whether the cytotoxic properties of ASA and DOX were synergistic when used together in HepG2, human HCC cell line, in vitro and HepG2 cell xenograft model in BALB/c nude mice in vivo.…”
Section: Introductionmentioning
confidence: 99%